2010
DOI: 10.1080/00220380903197978
|View full text |Cite
|
Sign up to set email alerts
|

The Vanishing Farms? The Impact of International Migration on Albanian Family Farming

Abstract: This paper investigates the impact of international migration on technical efficiency, resource allocation and income from agricultural production of family farming in Albania. The results suggest that migration is used by rural households as a pathway out of agriculture: migration is negatively associated with both labour and non-labour input allocation in agriculture, while no significant differences can be detected in terms of farm technical efficiency or agricultural income. Whether the rapid demographic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 21 publications
(21 reference statements)
3
27
1
1
Order By: Relevance
“…Many studies have found that migration increases household investments through remittances (Dustmann and Kirchkamp 2001;Lucas 1987;Woodruff and Zenteno 2007;Yang 2008), while others have argued that migration diminishes household investments by reducing the labor endowment (Miluka et al 2010;Rozelle et al 1999) or efficiency (Itzigsohn 1995). Our hypotheses connect these two sets of findings, and suggest that the impact of migration on household wealth depends on the household's initial wealth status.…”
Section: Generating Hypotheses From Qualitative Datamentioning
confidence: 50%
“…Many studies have found that migration increases household investments through remittances (Dustmann and Kirchkamp 2001;Lucas 1987;Woodruff and Zenteno 2007;Yang 2008), while others have argued that migration diminishes household investments by reducing the labor endowment (Miluka et al 2010;Rozelle et al 1999) or efficiency (Itzigsohn 1995). Our hypotheses connect these two sets of findings, and suggest that the impact of migration on household wealth depends on the household's initial wealth status.…”
Section: Generating Hypotheses From Qualitative Datamentioning
confidence: 50%
“…[Berti,45,living in village] This is compounded by the stigma attached to farming, especially by the youth. 4 Under such circumstances, migration is used both as a risk diversification strategy and, overwhelmingly, to pull rural households out of agriculture and take them to the city (see also Miluka, Carletto, Davis & Zezza 2007).…”
Section: Migration and Inequality In Rural Areasmentioning
confidence: 99%
“…A number of studies have provided empirical support to the positive impact of remittance on production despite its negative impact on labor availability at farm level (Miluka et al, 2007). Labor emigration benefits local economy in a variety of ways.…”
Section: Results and Affects Of Depopulationmentioning
confidence: 99%
“…Labour migration has multi-facet, positive and significant influences on agricultural development and agricultural production (Sheng, 2007). Nevertheless, some studies worry that these constructive impacts may be countervailed by potentially unfavourable affects on individual households or local communities, for example diminished household labour supply, weakened human capital and diminished labour efforts by members left behind (Miluka et al, 2007).…”
Section: Results and Affects Of Depopulationmentioning
confidence: 99%